1925 Ind. Acts 496, § 5-6 - (:unkn) unknown (My University, 1925)
Prohibited concealed carrying of a pistol or revolver without a permit. Violators guilty of a misdemeanor, punishable by fine of one hundred dollars and possible imprisonment not more than one year. The pistol or revolver shall be confiscated and destroyed.
Keywords: CARRY - CONCEALED